2011
DOI: 10.2225/vol14-issue5-fulltext-2
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamic acid, ethanol and temperature interaction on coumarate decarboxylase activity and the relative expression of the putative cd gene in D. bruxellensis

Abstract: Dekkera bruxellensis is one of the main contaminating yeasts in wine due to its ability to metabolize cinnamic acids into volatile phenols. This yeast metabolizes p-coumaric acid into 4-vinylphenol through a coumarate decarboxylase (CD) and then transforms it into to 4-ethylphenol (EF) through a vinylphenol reductase. In this work we investigated the influence of the interaction between the concentration of p-coumaric acid, ferulic acid and ethanol as well as growth temperature on the production of CD activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 27 publications
1
4
0
Order By: Relevance
“…Results obtained by Ganga et al (2011) are similar to that obtained by Dias et al (2003) and GardeCerdán et al (2008), where although D. bruxellensis presents basal coumarate decarboxylase activity, it is necessary to add ethanol to the culture medium to increase its production. Ganga et al (2011) investigated the influence of the interaction between the concentration of p-coumaric acid, ferulic acid and ethanol as well as growth temperature on the production of CD activity and the expression of a putative gene that codes for this enzymatic activity.…”
Section: Temperature Ethanol Concentration Phsupporting
confidence: 88%
See 1 more Smart Citation
“…Results obtained by Ganga et al (2011) are similar to that obtained by Dias et al (2003) and GardeCerdán et al (2008), where although D. bruxellensis presents basal coumarate decarboxylase activity, it is necessary to add ethanol to the culture medium to increase its production. Ganga et al (2011) investigated the influence of the interaction between the concentration of p-coumaric acid, ferulic acid and ethanol as well as growth temperature on the production of CD activity and the expression of a putative gene that codes for this enzymatic activity.…”
Section: Temperature Ethanol Concentration Phsupporting
confidence: 88%
“…Ganga et al (2011) investigated the influence of the interaction between the concentration of p-coumaric acid, ferulic acid and ethanol as well as growth temperature on the production of CD activity and the expression of a putative gene that codes for this enzymatic activity. These authors concluded that the interaction of cinnamic acids with growth temperature, and growth temperature with ethanol concentration, as well as ethanol concentration, are highly important variables in the production of CD activity.…”
Section: Temperature Ethanol Concentration Phmentioning
confidence: 99%
“…bruxellensis ( Dias et al, 2003b ; Godoy et al, 2008 ; Sturm et al, 2014 ). This evidence has posed the need to investigate the interaction among multiple aspects on the production of VPs ( Ganga et al, 2011 ; Chandra et al, 2014 ). For example, the influence of interactions due to the presence of p -coumaric acid, ferulic acid, and ethanol on CD activity and the expression of its putative gene has been studied ( Ganga et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…This evidence has posed the need to investigate the interaction among multiple aspects on the production of VPs ( Ganga et al, 2011 ; Chandra et al, 2014 ). For example, the influence of interactions due to the presence of p -coumaric acid, ferulic acid, and ethanol on CD activity and the expression of its putative gene has been studied ( Ganga et al, 2011 ). Results outlined that although oenological concentrations of p -coumaric and ferulic acids alone did not produced any significant effect on the enzyme activity, this was influenced by interactions between ethanol and cinnamic acid or temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Ganga et al (2011) have designed a response surface methodology (RSM) to evaluate the effect of enological factors on the activity and expression of decarboxylase in Dekkera. Through RSM, it is possible to evaluate the effects of several factors either individually or collectively.…”
Section: Introductionmentioning
confidence: 99%